(untitled) (Al Fiddhoh: Journal of Banking, Insurance, and Finance, 2021)
This study was conducted to examine the effect of financial literacy on student interest in investing in Islamic stocks at the Sharia Investment Gallery of IAIN Kerinci. Therefore, the sample used in this study amounted to 70 people. This research data analysis tool uses simple linear regression analysis. Where the results of the study indicate that financial literacy has a positive and significant effect on student interest in investing in sharia shares at the Sharia Investment Gallery of IAIN Kerinci, with the magnitude of the influence being 42.4%.